Pension funds' asset allocation and participant age: a test of the life-cycle model - Jacob A. Bikker; D.W.G.A Broeders; D. A. Hollanders; E. H.M. Ponds (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2009)
This paper examines the impact of participants' age distribution on the asset allocation of Dutch pension funds, using a unique data set of pension fund investment plans for 2007. Theory predicts a negative effect of age on (strategic) equity exposures. We observe that pension funds do indeed take the average age of their participants into account. However, the average age of active participants has been incorporated much more strongly in investment behaviour than the average ages of retired or dormant participants. This suggests that both employers and employees, who dominate pension fund boards, tend to show more interest in active participants. A one-year higher average age in active participants leads to a significant and robust reduction in the strategic equity exposure by around 0.5 percentage point. Larger pension funds show a stronger age-equity exposure effect than smaller pension funds. This age-dependent asset allocation of pension funds aligns with the original life-cycle model by which young workers should invest more in equity than older workers because of their larger human capital. Other factors, viz. fund size, funding ratio, and average pension wealth of participants, influence equity exposure positively and significantly, in line with theory. Pension plan type and pension fund type have no significant impact.
Keywords: 330; Pension funds; strategic equity allocation; lifecycle saving and investing